LONGITUDINAL DATA ANALYSIS OF STEVIA REBAUDIANA EVAPOTRANSPIRATION ACCORDING TO WATER LEVELS - PEREIRA, Omar Cléo Neves; PEREIRA, Paulo Vitor da Costa; BERTONHA, Altair; PREVIDELLI, Isolde Terezinha Santos (Brazilian Journal of Biometrics, 2018)
The purpose of this work was to evaluate the accumulated evapotranspiration of stevia, planted in 40 pots, over a period of 27 days according to four irrigation levels through a nonlinear mixed eects model and, with this model, to verify if we can maximize the stevia's evapotranspiration with a lower than usual water level. When the humidity of the substrate reached 50% of its maximum capacity retention, we added water to raise the humidity according to the four treatments: W1 = 62:5%; W2 = 75:0%; W3 = 87:5%; W4 = 100:0%. Although the crop production depends on the availability of water in the soil, there is a limit for the total yield. The water levels, W3 and W4, resulted in similar total accumulated evapotranspiration, while all the last three water levels, W2, W3 and W4 had close shoot dry matter masses at the end of the experiment. We showed that is possible to nd an optimal level of crop production with a rational use of the available water resources.